The association between different types of cooking fuels and common health problems: north India region - Mawari, Govind; Kumar, Naresh; Pathak, Ujala; Shree, Swati; Sarkar, Sayan; Daga, Mradul Kumar; Singh, Mongjam Meghachandra; Joshi, Tushar Kant; Gulati, Achal; Chowdhury, Apurba; Singh, Ishwar; Kumar, Ashutosh (International Journal Of Community Medicine And Public Health, 2023)
Background: The fuel used for cooking is a major source of indoor air pollution because of inefficient combustion and inadequate ventilation. This study was conducted to see if there is any association between the type of cooking fuel and common health problems in light of inadequate ventilation. Methods: This was a cross-sectional study; 688 subjects were selected randomly from various sectors and the outlying areas of Surajkund. The impact of indoor air pollution on health was assessed by questionnaires, general physical examination, and pulmonary function testing. Results: One of the key findings of the study has been the implication of LPG, touted as a safe, non-polluting fuel with a definite negative impact on health. There was significantly more breathlessness experienced by LPG users as opposed to the users of wood and cow dung. Though the prevalence of fever in both groups was similar, chest pain, burning of eyes, and fatigue were reported by wood and cow dung users much more frequently. The pulmonary function test showed restrictive pathology in cow dung and wood users, whereas obstructive pathology in LPG users. Conclusions: LPG is considered “clean” fuel because it does not produce visible emissions. However, improper burner design, blocking and clogging of the flue vent, and insufficient combustion air result in improper combustion and the emission of aldehydes, CO, hydrocarbons, and other organics. It would be folly to believe that LPG is harmless. Even a harmless material may become harmful if used inappropriately.